2022
DOI: 10.1186/s12904-022-01023-1
|View full text |Cite
|
Sign up to set email alerts
|

Where would Canadians prefer to die? Variation by situational severity, support for family obligations, and age in a national study

Abstract: Background Death at home has been identified as a key quality indicator for Canadian health care systems and is often assumed to reflect the wishes of the entire Canadian public. Although research in other countries has begun to question this assumption, there is a dearth of rigorous evidence of a national scope in Canada. This study addresses this gap and extends it by exploring three factors that moderate preferences for setting of death: situational severity (entailing both symptoms and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…For instance, consistent assumptions that patients almost universally prefer to be at home have been used to advocate for an expansion of home-based palliative care resources 4 and a focus on avoiding institutional care that underpins health care system quality indicators in Canada. 1 Interpretations of dying at home in such approaches, as well as in policy documents, are grounded in neoliberal conceptions of choice 9 and do not effectively convey the complexities of place of death preferences in the public 38 or as expressed by participants in the present study. Whereas the dominant approach in policy and practice is to conceive of place of death preferences as static and individual, a contingent and relational understanding emerges in participants’ talk about a relational meaning of home as being close to others; the importance of social integration of dying persons; and a need to consider, protect, and care for family members.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, consistent assumptions that patients almost universally prefer to be at home have been used to advocate for an expansion of home-based palliative care resources 4 and a focus on avoiding institutional care that underpins health care system quality indicators in Canada. 1 Interpretations of dying at home in such approaches, as well as in policy documents, are grounded in neoliberal conceptions of choice 9 and do not effectively convey the complexities of place of death preferences in the public 38 or as expressed by participants in the present study. Whereas the dominant approach in policy and practice is to conceive of place of death preferences as static and individual, a contingent and relational understanding emerges in participants’ talk about a relational meaning of home as being close to others; the importance of social integration of dying persons; and a need to consider, protect, and care for family members.…”
Section: Discussionmentioning
confidence: 91%
“…This project was part of a larger multi-method Canadian study exploring public preferences for and meanings of dying in different locations. 38 Within that project, we interviewed a group of stakeholders whose perspectives are less often integrated into research on dying at home, which focuses more on the perspectives of (often homogeneous samples of) dying patients and their physicians. We sought both professional and non-professional community members who, due to their frequent interaction with marginalized or journals.sagepub.com/home/pcr 3 diverse subgroups or experience acting as a group advocate or representative, worker, or volunteer with these groups, were well suited to speak to these groups' specific concerns.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…In contrast to the "naturalization of policies" (Blunkett, 2000) through abstract appeals to evidence, future policies and planning mechanisms need to be grounded in and provide clear indication of evidence informing the policy directions; this is part of effective long-term policy planning for aging populations (Marier, 2021). Our other research (Funk et al, 2022) shows how people's stated preferences for dying at home decrease when they consider complex situations of EOL care and dying at home. Whether and how existing public policies are sufficiently grounded in a rich and nuanced evidence-base is unclear.…”
Section: Discussionmentioning
confidence: 95%
“…As part of a larger mixed methods project studying preferences for and meanings of dying at home in Canada (Chan et al, 2023; Funk et al, 2022; Funk et al, 2023), we identified public policy related to dying at home (including both palliative and end‐of‐life care) within written documentation in which the federal and provincial/territorial governments state public directives for the health care system. This included 12 policies or formal statements, 19 websites, 15 action/strategic plans, and 13 bilateral health agreements (Table 1).…”
Section: Methodology and Designmentioning
confidence: 99%
“…22,23 Multiple studies have evidenced that most patients with and without cancer do not prefer to die in hospital. 2427 This has been substantiated by a systematic review of 210 studies from 33 countries that demonstrated moderate evidence that the majority of individuals preferred to die at home 28 and a meta-analysis of three studies that demonstrated that a slight majority of patients without cancer preferred to die at home. 29 To our knowledge, no study has demonstrated a predominant preference for death in the acute care setting.…”
Section: Introductionmentioning
confidence: 95%